2020
DOI: 10.7759/cureus.8974
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on the Mental Health of Healthcare Professionals in Pakistan

Abstract: Introduction As a result of the ongoing COVID-19 pandemic, health care professionals (HDPs) are facing immense strain due to the heavy load of cases. In many cases, they work increasingly long hours, often with limited resources and a dubious infrastructure. Thus, it is important to check on the mental health of caregivers. Methods and materials This cross-sectional study was conducted in May 2020, at various hospitals in Karachi, Pakistan. All HCPs posted in the COVID-19 isolation wards were invited to partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
119
4
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(140 citation statements)
references
References 13 publications
14
119
4
3
Order By: Relevance
“…(2020) ( Romero et al., 2020 ) Spain Cross-sectional COVID-19 3,109 health care workers 10 days, April 2020 A Psychological Stress and Adaptation at Work Score (PSAS) based on the: Healthcare Stressful Test, Coping Strategies Inventory, Font-Roja Questionnaire and the Trait Meta-Mood Scale Rossi et al. (2020) ( Rossi et al., 2020 ) Italy Cross-sectional COVID-19 1,378 health care workers (472 nurses, 433 physicians, 86 General Practitioners, 275 other [lab technicians, physiotherapists, radiotherapists] and 112 Health Care Assistants) 5 days, March 2020 GPS, PHQ-9, GAD-7, ISI and PSS Sandesh et al. (2020) ( Sandesh et al., 2020 ) Pakistan Cross-sectional COVID-19 112 health care workers May 2020 DASS-21 Schechter et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2020) ( Romero et al., 2020 ) Spain Cross-sectional COVID-19 3,109 health care workers 10 days, April 2020 A Psychological Stress and Adaptation at Work Score (PSAS) based on the: Healthcare Stressful Test, Coping Strategies Inventory, Font-Roja Questionnaire and the Trait Meta-Mood Scale Rossi et al. (2020) ( Rossi et al., 2020 ) Italy Cross-sectional COVID-19 1,378 health care workers (472 nurses, 433 physicians, 86 General Practitioners, 275 other [lab technicians, physiotherapists, radiotherapists] and 112 Health Care Assistants) 5 days, March 2020 GPS, PHQ-9, GAD-7, ISI and PSS Sandesh et al. (2020) ( Sandesh et al., 2020 ) Pakistan Cross-sectional COVID-19 112 health care workers May 2020 DASS-21 Schechter et al.…”
Section: Resultsmentioning
confidence: 99%
“…(2020) ( Rossi et al., 2020 ) Italy Cross-sectional COVID-19 1,378 health care workers (472 nurses, 433 physicians, 86 General Practitioners, 275 other [lab technicians, physiotherapists, radiotherapists] and 112 Health Care Assistants) 5 days, March 2020 GPS, PHQ-9, GAD-7, ISI and PSS Sandesh et al. (2020) ( Sandesh et al., 2020 ) Pakistan Cross-sectional COVID-19 112 health care workers May 2020 DASS-21 Schechter et al. (2020) ( Shechter et al., 2020 ) United States of America Cross-sectional COVID-19 657 health care workers, including physicians, advanced practice providers, residents, fellows and nurses 15 days, April 2020 PC-PTSD, PHQ-2, GAD-2 and questions modified from PSQI and ISI Shih et al.…”
Section: Resultsmentioning
confidence: 99%
“…In the sensitivity analysis, the lowest prevalence (39.8%, 95% CI: 33.2-46.6) was observed after excluding the study by Sandesh and colleagues 65 , whereas the highest prevalence (43.3%, 95% CI:…”
Section: Sensitivity Analysis and Publication Biasmentioning
confidence: 86%
“…Pooled prevalence of anxietyA total of 31 studies reported the prevalence of anxiety during COVID-19 in different samples from South Asian countries[46][47][48][49][50][51][52][53][54][55][56]58,59,[61][62][63][64][65][66]68,69,[71][72][73][74][75][76][77][78][79][80] . These studies used different scales to measureanxiety in respective samples, including the Generalized Anxiety Disorder 7-item (GAD-7) scale (n = 16), Depression, Anxiety and Stress Scale -21 Items (DASS-21) scales (n = 9), Hospital Anxiety and Depression Scale (HADS) (n = 4), Patient Health Questionnaire-4 (PHQ-4) (n = 1), and Self Reporting Questionnaire 20-items (SRQ-20) scale (n = 1).…”
mentioning
confidence: 99%
“… 12 Studies from the Indian subcontinent also showed approximately one-third of doctors had anxiety or depression during the COVID-19 pandemic, 13 and a report from Pakistan conducted on health care staff working in COVID-19 isolation wards, quantifying depression, anxiety and stress, showed 90.1% of participants reported moderate to extreme levels of psychological stress. 14 …”
Section: The Prevalence and Type Of Psychiatric Morbidities In Cancermentioning
confidence: 99%